Logischer Empirismus, Lebensreform und die deutsche Jugendbewegung Logical Empiricism, Life Reform, and the German Youth Movement - Damböck, Christian; Sandner, Günther; Werner, Meike G. (Veröffentlichungen des Instituts Wiener Kreis,, 2022)
This open-access book is the first to investigate the roots of Logical Empiricism in the context of the Life Reform and the German Youth Movements. Rudolf Carnap and Hans Reichenbach are the key protagonists; they both belonged to the German Youth Movement and developed their early philosophical views in this setting. By combining scholarly essays with unpublished and hard to access manuscripts, letters, and articles, this volume recasts our understanding of the early years of Logical Empiricism.